Mucoadhesive Bilayered Patches for Administration of Sumatriptan Succinate - Shidhaye, Supriya S. (Springer US, 2008)
The purpose of this study was to develop and optimize formulations of mucoadhesive bilayered buccal patches of sumatriptan succinate using chitosan as the base matrix. The patches were prepared by the solvent casting method. Gelatin and polyvinyl pyrrolidone (PVP) K30 were incorporated into the patches, to improve the film properties of the patches. The patches were found to be smooth in appearance, uniform in thickness, weight, and drug content; showed good mucoadhesive strength; and good folding endurance. A 3(2) full factorial design was employed to study the effect of independent variables viz. levels of chitosan and PVP K30, which significantly influenced characteristics like swelling index, in-vitro mucoadhesive strength, in vitro drug release, and in-vitro residence time. Different penetration enhancers were tried to improve the permeation of sumatriptan succinate through buccal mucosa. Formulation containing 3% dimethyl sulfoxide showed good permeation of sumatriptan succinate through mucosa. Histopathological studies revealed no buccal mucosal damage. It can be concluded that buccal route can be one of the alternatives available for administration of sumatriptan succinate.